Раскопки базилики Крузе в 2008 г. - Ушаков, С.В.; Тюрин, М.И. (Археологічні дослідження в Україні, 2009)
The article presents the results of field research of Kruse Basilica in Chersonesos in 2008. The investigation of filling under the floor of the southern aisle confirmed that basilica was built at the second half of the 5th c. — the first half of the 6th c. AD. At the area in front of the church the layer of the end of the 3rd c. and the beginning of the 2nd c. BC with numerous fragments of ceramics and a heap of mud bricks was discovered. The cistern, filled during the building of basilica, the base of the stone fence of the church complex, and dwellings of previous periods have been uncovered.